Do they care what they believe? Exploring the impact of religiosity on intention to purchase luxury products - Saba Ashraf; Muhammad Haroon Hafeez; Asif Yaseen; Amna Naqvi (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2017)
This paper aims to examine whether religion influences the purchase decision of potential customers. It is generally believed that Islam is a religion which provides holistic guidelines to its followers regarding all facets of life. Thus, it is interesting to know how strongly Islam impacts consumers' decision making. Islamic marketing is an emerging discipline which has initiated numerous interesting scholarly debates and resulted in conducting empirical studies in order to gauge the extent to which Muslim consumers follow religious teachings when it comes to decision making regarding purchase of products and services. In the same vein, this paper has examined the impact of religion on purchase intention of luxury products in Pakistan. In a bid to collect the data, mall intercept survey was performed. Data was analyzed using Smart PLS. Findings of the study indicate that religiosity does not moderate the relationship between attitude, belief, perceived behavioral control, subjective norms and purchase intention towards luxury products. This paper would provide useful implications to marketers of luxury products as they would get an insight regarding the effect of religion on consumers' purchase decisions; thus, they can come up with effective marketing strategies and offer products and services which are compatible with consumers' religious beliefs.
Keywords: 330; religiosity; purchase intention; luxury goods; Muslim consumers; religious beliefs